Antagonists of Wnt/β‐catenin signalling in the periodontitis associated with type 2 diabetes and smoking. (12th January 2018) - Miranda, Tamires S.; Napimoga, Marcelo H.; Feres, Magda; Marins, Letícia M.; da Cruz, Daniele F.; da Silva, Hélio Doyle P.; Duarte, Poliana M.
Abstract: Aim: This study evaluated the levels of sclerostin (SOST) and Dickkopf (DKK)‐1 in the chronic periodontitis (CP) associated with type 2 diabetes (DM) and/or smoking. Relationships between SOST, DDK1, RANKL, OPG, IL‐1ß, IL‐6 and TNF‐α, and pathogens were assessed. Material and Methods: The study population included non‐diabetic non‐smokers (control), non‐smokers with DM (DM group), non‐diabetic smokers (S group) and smokers with DM (SDM group), all with CP. Serum and gingival levels of SOST, DKK1, RANKL, OPG, IL‐1ß, IL‐6 and TNF‐α were evaluated by multiplex immunoassay. Gene expressions of these biomarkers and subgingival levels of pathogens were assessed by qPCR. Results: Gingival protein and/or mRNA levels of DKK1 and SOST were higher in subjects with DM and/or smoking than in controls ( p  < .05). Serum levels of SOST were higher in the DM group than in controls ( p  < .05). DKK1 positively correlated with SOST in the DM, SDM and control groups ( p  < .05) at mRNA levels. DKK‐1 and SOST correlated with pathogens, especially in both groups with DM. Conclusions: SOST and DKK1 were upregulated in patients with CP presenting DM and/or smoking. DM, alone or with smoking, particularly influenced the correlations of SOST and DKK1 with each other and with the other biomarkers mostly at mRNA levels, as well as with periodontal pathogens.